PEMBELAJARAN ONLINE PAI DI SMAN 1 TEMPEL PADA MASA PANDEMI COVID 19 - Suwahyu, Irwansyah (Inspiratif Pendidikan, 2023)
This study examines PAI online learning at SMAN 1 Tempel during the covid-19 pandemic. This study uses descriptive qualitative research methods. Where the data collection in this study was carried out using an interview technique with PAI teachers at SMAN 1 Tempel. In this study, it was found that PAI learning at SMAN 1 Tempel was completely done online. Then the PAI teacher in the learning process utilizes several learning applications such as google classroom, whatsapp, zoom meeting, and youtube. This is to streamline the online learning process. Among the methods used are lectures, questions and answers, and assignments. However, in the PAI online learning process there are also various obstacles found. Such as the availability of internet networks, expensive data packages, and the emergence of a sense of laziness and boredom. So that good communication between teachers, students and parents are needed to support online learning.